Step by step - Wolkstein, Diane; Smith, Joseph A. (Joseph Anthony), 1936- (New York : Morrow Junior Books, 1994)
A little ant and her friend enjoy a day together, dining on the nectar of a yellow flower, sailing on a leaf, and dancing in the rain.
Keywords: Ants -- Fiction; Insects -- Fiction; Friendship -- Fiction